2012
DOI: 10.1136/bcr-2012-007247
|View full text |Cite
|
Sign up to set email alerts
|

Subacute bacterial endocarditis secondary to mastoiditis: a rare complication

Abstract: Mastoiditis can result from untreated otitis media. If unrecognised, it can result in life-threatening complications. We present a 69-year-old woman with a history of left-sided otitis media admitted to intensive care unit following collapse with a decreasing Glasgow Coma Scale. Myringotomy and ventilator insertion revealed pus in the middle ear, which grew Group A Streptococcus. Her fever persisted and blood samples cultured Group A Streptococcus. Echocardiogram confirmed subacute bacterial endocarditis. Suba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…Infective endocarditis is a rare complication of CSOM. The present case study is in consonance with the findings of a previous case study which reported subacute bacterial endocarditis as a rare complication of mastoiditis [12]. The current study reveals that CSOM is risky and can lead to infective endocarditis; identification of this potential complication can prevent morbidity and mortality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Infective endocarditis is a rare complication of CSOM. The present case study is in consonance with the findings of a previous case study which reported subacute bacterial endocarditis as a rare complication of mastoiditis [12]. The current study reveals that CSOM is risky and can lead to infective endocarditis; identification of this potential complication can prevent morbidity and mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Infective endocarditis (IE) is a multisystem disease that results from bacterial infection of the endocardial surface of the heart. Smith et al [12] found infective endocarditis in a patient with mastoiditis. Guler et al [13] found bicuspid aortic valve complications due to infective endocarditis arising from underlying chronic otitis media.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the etiology of our patient's endocarditis may have been due to meningitis as research has shown that there is a 2% incidence rate of endocarditis with meningitis 8 . A thorough literature review revealed only one other case report that demonstrated that mastoiditis may also directly cause endocarditis 9 . Our patient further underwent a transthoracic echocardiogram because of the presence of Streptococcus pneumonia bacteremia.…”
Section: Discussion/conclusionmentioning
confidence: 82%
“…8 A thorough literature review revealed only one other case report that demonstrated that mastoiditis may also directly cause endocarditis. 9 TTE had returned negative, we would have proceeded with a transesophageal echocardiogram since it is more sensitive for endocarditis and our clinical suspicion for endocarditis was high. 10 Therefore, it is critical to recognize the possible presence of Austrian syndrome even if all three elements of the classic triad are not present as early recognition significantly improves patient outcomes.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…19 Systemically, it is important to highlight that infection from acute mastoiditis can spread outside the head and neck, resulting in medical emergencies, such as sepsis or rare distant complications such as bacterial endocarditis. 20…”
Section: Other Head and Neck Imagingmentioning
confidence: 99%